2011
DOI: 10.1002/casp.1073
|View full text |Cite
|
Sign up to set email alerts
|

Constructing the stereotype of immigrants' criminality: Accounts of fear and risk in talk about immigration to Greece

Abstract: This paper explores the discursive construction of immigrants' criminality in interview accounts obtained by a sample of Greek people in Thessaloniki (Northern Greece). Analysis, which adopts a discursive approach to stereotypes and category construction, indicates that fear and insecurity on the part of Greek people are represented as a sine qua non consequence of immigration to Greece. Two different lines of argument are used to account for the arousal of fear. According to the first, fear constitutes a coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 27 publications
5
27
0
1
Order By: Relevance
“…Ideas about illegality and the notion of the “uninvited guest” are in line with existing research on representations of asylum seekers and other migrants, both in the Greek context, where they are represented as criminal and violent (Figgou et al, ; Pavlou, ) but also generally in Western societies (Hanson‐Easey & Augoustinos, ) where they are represented as illegal or bogus and opportunist (Lynn & Lea, ).…”
Section: Essentialism In Ethnic Civic and Cultural Representations supporting
confidence: 79%
See 1 more Smart Citation
“…Ideas about illegality and the notion of the “uninvited guest” are in line with existing research on representations of asylum seekers and other migrants, both in the Greek context, where they are represented as criminal and violent (Figgou et al, ; Pavlou, ) but also generally in Western societies (Hanson‐Easey & Augoustinos, ) where they are represented as illegal or bogus and opportunist (Lynn & Lea, ).…”
Section: Essentialism In Ethnic Civic and Cultural Representations supporting
confidence: 79%
“…Such debates are particularly challenging in the Greek context. On the one hand, Greek national identity is predominantly based on an ethnic representation of the Greek nation (Chryssochoou, ; Triandafyllidou & Veikou, ) and is commonly constructed against the “immigrant other” (Figgou, Sapountzis, Bozatzis, Gardikiotis, & Pantazis, ; Triandafyllidou & Veikou, ; Tzanelli, ). On the other hand, the intense political, social, and economic crisis along with the rise of extremist right‐wing politics has intensified the preexisting anti‐immigration feelings in the country.…”
mentioning
confidence: 99%
“…An important finding of this research is that people try to distance themselves from negative stereotypes about immigrants treating them as problematic, as an instance of an irrational generalization. At the same time though, their own or others' fears of immigrants were justified on the premises that some of the immigrants may be involved or are more likely to be involved in criminal activities due to economic deprivation (Di Masso, Castrechini, & Valera, ; Figgou & Condor, ; Figgou, Sapountzis, Bozatzis, Gardikiotis, & Pantazis, ).…”
Section: The Norm Against Prejudice In Discourse Analytic Workmentioning
confidence: 99%
“…Comparative survey research, for example, has demonstrated that anti-foreigner sentiment is higher in Greece than anywhere else in Europe (Semyonov et al, 2006;Mulcahy, 2011), and that Greeks hold the most negative views on the continent regarding the impact of foreigners on society, including their impact on crime (Semyonov et al, 2012; see also Semyonov et al, 2008;Semyonov and Glikman, 2009;Ceobanu, 2011;Mulcahy, 2011;Swarts and Karakatsanis, 2013;Figgou et al, 2011). Domestic survey research has meanwhile found that Greeks are more likely to favour stricter police treatment for immigrants than for natives, just as they are more likely to favour imprisonment for immigrant offenders than for offenders from other socio-demographic groups (see further Cheliotis and Xenakis, 2011).…”
Section: Political Discourse and Public Attitudes About Immigrantsmentioning
confidence: 99%